2013
DOI: 10.1186/1556-276x-8-66
|View full text |Cite
|
Sign up to set email alerts
|

Thiolated chitosan-modified PLA-PCL-TPGS nanoparticles for oral chemotherapy of lung cancer

Abstract: Oral chemotherapy is a key step towards ‘chemotherapy at home’, a dream of cancer patients, which will radically change the clinical practice of chemotherapy and greatly improve the quality of life of the patients. In this research, three types of nanoparticle formulation from commercial PCL and self-synthesized d-α-tocopheryl polyethylene glycol 1000 succinate (PLA-PCL-TPGS) random copolymer were prepared in this research for oral delivery of antitumor agents, including thiolated chitosan-modified PCL nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 43 publications
4
37
0
Order By: Relevance
“…Previous clinical studies have shown that drug-loaded nanoparticles may be administered orally or injected. 22,23 Nanoparticles modified by thiolated chitosan can enhance cellular uptake and cytotoxicity, and have the potential for oral administration in the treatment of cancer. 22 On the other hand, the injectable form can be tailored to control drug release and thereby increase selective cell targeting, cell uptake, drug solubility, and circulation time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical studies have shown that drug-loaded nanoparticles may be administered orally or injected. 22,23 Nanoparticles modified by thiolated chitosan can enhance cellular uptake and cytotoxicity, and have the potential for oral administration in the treatment of cancer. 22 On the other hand, the injectable form can be tailored to control drug release and thereby increase selective cell targeting, cell uptake, drug solubility, and circulation time.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Nanoparticles modified by thiolated chitosan can enhance cellular uptake and cytotoxicity, and have the potential for oral administration in the treatment of cancer. 22 On the other hand, the injectable form can be tailored to control drug release and thereby increase selective cell targeting, cell uptake, drug solubility, and circulation time. 23 As a molecularly targeted anticancer drug, sorafenib requires oral administration at present.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In addition, TPGS has been reported to efficiently inhibit the growth of human lung cancer cells both in vivo and in vitro. 24 Furthermore, TPGS produces synergistic growth inhibition effects upon combination with other anticancer drugs due to its ability to induce apoptosis in tumor cells. 25 Although there have been many HA-based PNs exploited for drug delivery, this is the first report on the formulation of a multifunctional drug delivery system based on HA block copolymer and TPGS.…”
Section: Abbad Et Almentioning
confidence: 99%
“…The synergistic antitumor activity of TPGS in the presence of MH is due to its ability to induce ROS-generation and apoptosis. 54,55 Besides the two above reasons, another factor contributing to the improved cytotoxicity of MH-MNs over MH-PNs and free MH is the ability of both TPGS and MH to inhibit the P-gp protein expressed in A549 cells and reduce drug efflux. [56][57][58] cellular uptake HA-PBCA forms a core-shell structure block copolymer that can self-assemble into polymeric micelles or nanoparticles.…”
mentioning
confidence: 99%
“…The most commonly used polymers used in lung cancer nanotherapeutics include polylactic acid (PLA) [165][166][167], poly(lactide-co-glycoside) (PLGA) [168][169][170], poly(ethylene glycol) (PEG) [171][172][173][174][175][176], poly(ethyleneimine) (PEI) [177][178][179][180][181], chitosan [182][183][184][185][186], and gelatin [187][188][189][190]. Nguyen et al developed conjugates that coupled cell penetrating peptides (CPP) to PEI, through a PEG linker.…”
Section: Organic Nanoparticles For Lung Cancermentioning
confidence: 99%